General surgical anatomy and examination - Thompson, Alastair M.; Alastair Thompson (Edinburgh ; New York : Churchill Livingstone, 2002)
this book seeks to illustrate core anatomy and show its relevance to all those involved in the examination and history taking of surgical patients.
this book content head and neck -- chest--breast -- abdomen -- perineum -- hernia -- groin and scrotum -- lower limb -- skin and nails .
Includes index-- surgery -- anatomy.
All age.
Keywords: Anatomy, Surgical and topographical; Human anatomy